Oral valdecoxib and injected parecoxib for acute postoperative pain: a quantitative systematic review - Barden, J; Edwards, J; McQuay, H; Moore, R (BioMed Central, 2003)
Background: Clinical trials suggest that cyclo-oxygenase-2 specific inhibitors (coxibs) are an effective treatment for acute postoperative pain. The aims of this systematic review were to examine the evidence for oral valdecoxib and injected parecoxib, and quantify efficacy and adverse effects. Methods: Information from randomized, double-blind studies in acute postoperative pain was sought. The area under the pain relief versus time curve over four to six hours was dichotomized using validated equations to derive the proportion of patients with treatment and placebo with at least 50% pain relief over four to six hours and calculate the number-needed-to-treat (NNT). Information on duration of analgesia and adverse events was also collected. Results: The NNT for one patient to experience at least 50% relief over six hours following a single oral dose of valdecoxib 20 mg and 40 mg was 1.7 (1.4 to 2.0) and 1.6 (1.4 to 1.8) respectively. The NNT for one patient to have at least 50% relief over four to six hours with parecoxib 20 mg IV and 40 mg IV was 3.0 (2.3 to 4.1) and 2.3 (2.0 to 2.6) respectively. Mean time to remedication (weighted by trial size) was >24 hours with valdecoxib 40 mg, 8.7 hours with parecoxib 40 mg IV and 1.7 to 1.8 hours with placebo. There were no statistical differences between treatment and placebo for any adverse effect. Conclusion: Both oral valdecoxib and injected parecoxib are effective treatments for acute postoperative pain.